BEYOND MOSLEMS PANICS:AN EXPLORATION UPON INSTAGRAM MATCHMAKER IN INDONESIA - Muhammad Saifullah (Harmoni, 2018)
Nowadays, many Indonesian Moslems youth wielded social media, including instagram, not simply to express their piety or reach life goal, rather also for practical benefit just like marriage. This article focuses upon how they were stunned to gain bride or bridegroom through instagram. It tries to examine why they don’t choose merely their spouse over offline. I particularly discuss a single popular account regarding matchmaker taaruf_nikah (dating marriage) as deemed successful enough to arrange marriages amongst Indonesian Moslems. The account operationally provided service for its followers to post their picture after paying IDR100.000. Still, it opens an advertising services too and often posts pictures/videos portraying how proper Moslem is one who avoid dating and take an immediacy wedding because of god. Standing on thesis that instagram was the ultimate platform to shape public opinion, the article therefore argues that the main factor why it is triumph in taking many Indonesian Moslems youth’s heart lay onto its dissemination of anxieties amongst Moslem youth society through religion commodification notably in respect of who is the pious one and vice versa.